THE EFFECT OF COMPENSATION, WORKLOAD, AND WORK ENVIRONMENT ON TURNOVER INTENTION (STUDY ON EMPLOYEES GENERATION Z IN CIREBON REGENCY) - Hafidz Al Hizbullah Jubaedi; Awang Darmawan Putra (Management and Leadership Study Programme, 2026)
Turnover intention is challenge strategic in maintain employees, in particular Generation Z dominates power Work productive moment this. Pre-survey results show that employee Generation Z in Cirebon Regency intends to leave company, so that push the need study more deep about factors that influence it. Research This aim analyze influence compensation, burden work and environment Work to employee turnover intention Generation Z in Cirebon Regency. Research This use approach quantitative with data collection through questionnaire online to respondents​ use technique simple random sampling and analyzed with method Partial Least Square-Structural Equation Modeling (PLS-SEM) through SmartPLS 4.1. Research results show that compensation, burden work, environment each other's work is influential positive and significant to turnover intention study This give implications practical for management companies in Cirebon district for prioritize repair system compensation, arrangement burden proportional work and maintenance​ environment conducive work​ as the main strategy in pressing turnover intention employee Generation Z.